2014
DOI: 10.1371/journal.pone.0102788
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormone Levels and Reproductive Development of Eight-Year-Old Children following In Utero and Environmental Exposure to Phthalates

Abstract: In utero exposure to phthalates may adversely affect reproductive development in children due to the anti-androgenic properties of the pthalates. Accordingly, we aimed to determine the effects of in utero and environmental phthalate exposure on the reproductive development of eight-year-old children. We recruited 180 children in central Taiwan during November 2001 and followed them until August 2009 when all children became eight years old. Birth outcomes were collected. Bone age, hormone concentrations, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Much less is known about phthalates in relation to estradiol and progesterone activity in humans. A study of Taiwanese girls found that serum MEHP and MBzP levels were positively associated with serum progesterone (Su et al, 2014). In a study of pregnant women in Puerto Rico, MEP concentrations were inversely associated with progesterone across pregnancy (Johns et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about phthalates in relation to estradiol and progesterone activity in humans. A study of Taiwanese girls found that serum MEHP and MBzP levels were positively associated with serum progesterone (Su et al, 2014). In a study of pregnant women in Puerto Rico, MEP concentrations were inversely associated with progesterone across pregnancy (Johns et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in utero exposure to MEP and MBzP was associated with increased testosterone levels in girls at ages 8–13 years from the Mexico City birth cohort ( 176 ). Urinary levels of MEHP and MBzP in 8-year-old girls from Taiwan were also positively associated with increased serum progesterone levels and urinary levels of MBzP and MBP were positively associated with increased serum FSH levels ( 177 ).…”
Section: Effects Of Phthalates On Steroidogenesismentioning
confidence: 99%
“…Phthalate diester is reported to have anti-androgenic and weak estrogenic effects. 8 , 9 , 10 , 11 , 12 , 13 Small children may be particularly prone to exposure because of frequent hand-to-mouth activity and increased phthalate exposure dose per kilogram of body weight due to small body size. Swan and colleagues found that boys born to mothers with increased urinary levels of phthalate metabolites had reduced anogenital distance.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 A previous study of older children showed that di-n-butyl phthalate (DnBP) is negatively associated with adrenal androgen levels in boys. 16 For girls, increased urinary phthalate levels are associated with delayed pubarche 9 , 13 , 18 ; however, evidence on the effects of phthalates on thelarche is less conclusive. 19 , 20 , 21…”
Section: Introductionmentioning
confidence: 99%